DETERMINATION OF THE CONCENTRATION OF LEAD (PB) IN BLOOD AND URINE IN THE POPULATION RESIDING NEAR YAMUNA REGION OF DELHI-NCR - Dwivedi, Achala; Singhania, Shrisha; chandrawanshi, Lalit; Agrawal, Anugya; Agrawal, Prashant (Journal of Forensic Medicine and Toxicology, 2025)
The study was conducted to evaluate the levels of Lead in blood and urine in the individuals of different age groups who are residing near Yamuna region of Delhi-NCR. The goal of the study is to analyse the concentration of the lead in exposed area and to increase the awareness regarding the health risk caused by lead in inhabitants of Yamuna region. A total number of 144 subjects were included in the present study. Urine and blood sample 144 each were taken from the selected subjects of age group 16–45 years. Blood and urine sample were further digested in the laboratory by using wet digestion method. Digestate was analysed with the help of Atomic absorption spectrophotometer (AAS) for the presence of Lead in blood and urine sample. The mean concentration of Lead in blood was found 22.05±1.06 µg/dl. The maximum concentration of lead was 59.32 µg/dl while minimum concentration was 0.68 µg/dl. The mean concentration of the Lead in urine was 0.54±0.03 mg/l. The maximum concentration was 1.53 mg/l while minimum was below the detection limit. The result shows that the people who are residing near Yamuna region may have health risk due to more lead concentration in their urine and blood. We need to monitor the concentration of lead due to industrial waste which is being released into the Yamuna River causing health issues in the human.